Perawatan Sistem Poros Baling-Baling Kapal Ikan pada Kelompok Nelayan “Perahu Layar” Desa Mattito Tasi, Mattiro Sompe, Kabupaten Pinrang - Baharuddin, Baharuddin - (Faculty of Engineering UNHAS, 2023)
The Fishing boats in Pinrang district have begun to be equipped with engine-powered propulsion machines (motors). In terms of impact, the motorization of fishing boats has had a significant effect on the income level of fishermen, as seen from the increase in income and productivity of fishermen's catches. The motorization of the boat has facilitated fishing, accelerated reaching the fishing ground, and expanded the range of fishing areas. The use of a propeller shaft system on a fishing boat almost never takes into account the loading factor when the shaft is used. As a result, it is not uncommon for fishermen to then experience problems such as sudden engine failure or broken shafts in the middle of the sea. The things described above are common problems encountered and are very basic to immediately take counseling action through PPM LBE - Collaboration 2023 activities. The condition of the ship's propeller shaft system that is not maintained, in addition to being prone to ship safety, also causes the operation of the ship to be no longer efficient because it is wasteful in the use of fuel so that it is not feasible in terms of the propriety of ship operations.